The Lost-Sisters in the Public Sphere: a Study of Socio-Theological Christianity on the Roles of Women’s Politics - Mangililo, Ira D. (Jurnal Perempuan, 2014)
The purpose of this paper is to understand the role of Indonesian Christian women in the public sphere, especially in the realm of politics. This article aims to reconstruct the role of Israelite women who lived in pre-monarchic Israel using sociological, social science, anthropological, and archeological methods. The result of my analysis shows that the demands of war that occurred continuously in the territory of ancient Israel and the opening of new land in the mountainous regions of Israel required the active participation of women to not only be involved in the reproduction but also the production–an activity that belonged to male members of the family. This phenomenon creates a balance in the division of labor between men and women which of course increased the status of women in society. The result of this reconstruction that underlines the active role of women in the public sphere in the world of ancient Israel becomes an important model for Christian women in Indonesia today to take an active role in the public sphere, especially in politics.